An integrative reassessment of Leptobrachium bompu (Anura: Megophryidae) with new insights on phylogenetic position, male calls and larval morphology - Sarmah, A. N. Dikshit Akalabya; Tajo, Tage; K., Radhakrishna Upadhyaya; Garg, Sonali; Biju, S. D. (Zootaxa, 2025)
Since its description from the Eaglenest Wildlife Sanctuary in Arunachal Pradesh of India, Leptobrachium bompu Sondhi & Ohler, 2011 has been considered a rarely sighted species with presumed low population density. The species continues to be known from a handful of specimens and little has been studied about it thereafter. Notably, the molecular identity of L. bompu from the type locality itself remains unassessed. Through our recent field surveys in the state, we have been able to study and dispel the misconceptions around the rarity of this species by reporting several new individuals here, alongside new locality records. In addition, we assess and establish the molecular identity of the typical and other reported populations of L. bompu from India for the first time, and clarify their phylogenetic relationships, both with closely related populations from nearby regions and all other 38 currently recognised members of the genus. Our various analyses confirm that the reported Chinese populations from Medog county, Tibet, previously referred to as L. ‘bompu’(herein L. cf. bompu), are divergent from L. bompu sensu stricto of India by genetic distances of 3.6–4.2% for the analysed fragment of mitochondrial DNA, suggesting that they could represent another potential cryptic species requiring further taxonomic scrutiny. Furthermore, our study employed an integrative approach to better understand the systematic affinities and biology of the poorly-known L. bompu. Based on our newly gathered data from the Indian populations, we provide a redescription of adult morphology, tadpole morphology, and vocal repertoire of male advertisement calls of the species, including comparative insights with respect to other previously documented species of the genus. Our work, therefore, not only improves the current knowledge on L. bompu, but also has resultant implications on the identity of related Chinese populations, alongside some genus-wide insights on Leptobrachium frogs at large.